Multicentre cluster randomised trial comparing a community group exercise programme and home-based exercise with usual care for people aged 65 years and over in primary care - Steve Iliffe; Denise Kendrick; Richard Morris; Tahir Masud; Heather Gage; Dawn Skelton; Susie Dinan; Ann Bowling; Mark Griffin; Deborah Haworth; Glen Swanwick; Hannah Carpenter; et al. (Health Technology Assessment, 2014)
Background: Regular physical activity (PA) reduces the risk of falls and hip fractures, and mortality from all causes. However, PA levels are low in the older population and previous intervention studies have demonstrated only modest, short-term improvements. Objective: To evaluate the impact of two exercise promotion programmes on PA in people aged ≥ 65 years. Design: The ProAct65+ study was a pragmatic, three-arm parallel design, cluster randomised controlled trial of class-based exercise [Falls Management Exercise (FaME) programme], home-based exercise [Otago Exercise Programme (OEP)] and usual care among older people (aged ≥ 65 years) in primary care. Setting: Forty-three UK-based general practices in London and Nottingham/Derby. Participants: A total of 1256 people ≥ 65 years were recruited through their general practices to take part in the trial. Interventions: The FaME programme and OEP. FaME included weekly classes plus home exercises for 24 weeks and encouraged walking. OEP included home exercises supported by peer mentors (PMs) for 24 weeks, and encouraged walking. Main outcome measures: The primary outcome was the proportion that reported reaching the recommended PA target of 150 minutes of moderate to vigorous physical activity (MVPA) per week, 12 months after cessation of the intervention. Secondary outcomes included functional assessments of balance and falls risk, the incidence of falls, fear of falling, quality of life, social networks and self-efficacy. An economic evaluation including participant and NHS costs was embedded in the clinical trial. Results: In total, 20,507 patients from 43 general practices were invited to participate. Expressions of interest were received from 2752 (13%) and 1256 (6%) consented to join the trial; 387 were allocated to the FaME arm, 411 to the OEP arm and 458 to usual care. Primary outcome data were available at 12 months after the end of the intervention period for 830 (66%) of the study participants.: The proportions reporting at least 150 minutes of MVPA per week rose between baseline and 12 months after the intervention from 40% to 49% in the FaME arm, from 41% to 43% in the OEP arm and from 37.5% to 38.0% in the usual-care arm. A significantly higher proportion in the FaME arm than in the usual-care arm reported at least 150 minutes of MVPA per week at 12 months after the intervention [adjusted odds ratio (AOR) 1.78, 95% confidence interval (CI) 1.11 to 2.87; p = 0.02]. There was no significant difference in MVPA between OEP and usual care (AOR 1.17, 95% CI 0.72 to 1.92; p = 0.52). Participants in the FaME arm added around 15 minutes of MVPA per day to their baseline physical activity level. In the 12 months after the close of the intervention phase, there was a statistically significant reduction in falls rate in the FaME arm compared with the usual-care arm (incidence rate ratio 0.74, 95% CI 0.55 to 0.99; p = 0.042). Scores on the Physical Activity Scale for the Elderly showed a small but statistically significant benefit for FaME compared with usual care, as did perceptions of benefits from exercise. Balance confidence was significantly improved at 12 months post intervention in both arms compared with the usual-care arm. There were no statistically significant differences between intervention arms and the usual-care arm in other secondary outcomes, including quality-adjusted life-years. FaME is more expensive than OEP delivered with PMs (£269 vs. £88 per participant in London; £218 vs. £117 in Nottingham). The cost per extra person exercising at, or above, target was £1919.64 in London and £1560.21 in Nottingham (mean £1739.93). Conclusion: The FaME intervention increased self-reported PA levels among community-dwelling older adults 12 months after the intervention, and significantly reduced falls. Both the FaME and OEP interventions appeared to be safe, with no significant differences in adverse reactions between study arms. Trial registration: This trial is registered as ISRCTN43453770. Funding: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 18, No. 49. See the NIHR Journals Library website for further project information.